Changing spectrum of Zimmerman-Laband syndrome: a six years follow up case report of a family - Narendra, Suryakanta; Senapaty, Surendra nath; Bose, Chaitali; Samanta, Deepti; Moharana, Dhirendranath (International Journal of Research in Medical Sciences, 2017)
The Zimmermann-Laband syndrome (ZLS) is a rare genetic disorder inherited as an autosomal dominant fashion, with clinical characters like, gingival fibromatosis, bulbous soft nose, thick floppy ears, nail dysplasia, joint hyperextensibility, hepatosplenomegaly, skeletal anomalies and occasional mental retardation. Idiopathic gingival enlargement is a hereditary condition; it can be expressed as autosomal dominant inheritance. Here association of Idiopathic gingival enlargement has been reported in a family, with an autosomal dominant inheritance diagnosed to be ZLS. Other clinical features associated are, hypertrichosis, bulbous soft nose, thick floppy ears, nail dysplasia, joint hyper extensibility, bimaxillary protrusion and enlarged palm and fingers with flat feet. The unusual clinical presentations of massive gingival fibromatosis, unusual length of upper limbs and bimaxillary protrusion supported the variable spectrum of phenotype expression of the ZLS. The Biopsy report confirmed the diagnosis of gingival fibromatosis. Gingivectomy was carried out in all four quadrants for exposing the natural teeth and to bring back the original contour of the gingiva. But there was recurrence of the enlargement found to be associated during 6 years follow up.